2019
DOI: 10.1037/xlm0000644
|View full text |Cite
|
Sign up to set email alerts
|

When numbers are not exact: Ambiguity and prediction in the processing of sentences with bare numerals.

Abstract: It is generally assumed that bare numerals (e.g., three) have two readings: the exactly and the at least reading. It has been a matter of debate whether one of these two readings is derived from the other pragmatically. To shed light on this question research has aimed at characterizing the processing demands associated with these alternative interpretations. Here we use a sentence-picture verification paradigm where participants are asked to judge whether “N pictures contain Xs” is true in a situation where (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 92 publications
0
7
1
Order By: Relevance
“…Moreover, Cosentino et al (2017) and Werning et al (2019) have shown that it is not only the semantic similarity between the target word and the preceding context (frequency and thematic role assignments held constant) what determines suprisal, but also the relevance of the preceding context for the target word. Furthermore, false compared to true affirmative sentences have repeatedly been shown to lead to an elevated N400 component (Fischler et al, 1983; Hagoort et al, 2004; Nieuwland and Kuperberg, 2008; Metzner et al, 2015; Dudschig et al, 2016, 2019; Spychalska et al, 2016, 2019). For negated sentences, a reversed ERP-pattern has been observed with true negative sentences, such as for example A rose is not an insect , eliciting larger N400 components than false negative sentences, such as for example A rose is not a flower (Fischler et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Cosentino et al (2017) and Werning et al (2019) have shown that it is not only the semantic similarity between the target word and the preceding context (frequency and thematic role assignments held constant) what determines suprisal, but also the relevance of the preceding context for the target word. Furthermore, false compared to true affirmative sentences have repeatedly been shown to lead to an elevated N400 component (Fischler et al, 1983; Hagoort et al, 2004; Nieuwland and Kuperberg, 2008; Metzner et al, 2015; Dudschig et al, 2016, 2019; Spychalska et al, 2016, 2019). For negated sentences, a reversed ERP-pattern has been observed with true negative sentences, such as for example A rose is not an insect , eliciting larger N400 components than false negative sentences, such as for example A rose is not a flower (Fischler et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Incidentally, findings like those in [ 45 ] are edifying for the Experimental Pragmatics literature itself, in that they show that enriched readings build on, or are secondary to, at least readings. That study arbitrated between several competing accounts of number representation (for a summary of accounts, see [ 47 ]).…”
Section: Introductionmentioning
confidence: 83%
“…Two notable examples come from neuroimagery work on the pragmatic processing of numerical quantifiers. One comes from Spychalska et al [ 45 ], who presented participants with a sentence-picture verification task that begins with a numerically quantified sentence, such as Three pictures contain , before showing, say, 3 cats and 5 balls distributed over 6 frames (in a 2 x 3 matrix). To conclude the sentence, a final word was presented (which can be cats or balls here) and participants were then required to answer with a “yes” or “no.” When the sentence was completed with the word balls , the authors reported that two-thirds of participants (30 of 45) rejected the sentence and the remaining third accepted it.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Noveck and Posada (2003) compared event‐related potentials elicited by the final words of patently true sentences like Some people have brothers (it is true that some, but not all, people have brothers) and those of infelicitous sentences like Some staircases have steps (while the sentence is literally true, it is not true that ‘not all staircases have steps’). Later studies introduced more controlled designs (e.g., Nieuwland, Ditman, & Kuperberg, 2010), with the most recent studies in this vein using picture stimuli to control the contexts rather than relying on world knowledge as a context like the above examples do (Hunt, Politzer‐Ahles, Gibson, Minai, & Fiorentino, 2013; Spychalska, Kontinen, & Werning, 2016, Spychalska, Kontinen, Noveck, Reimer, & Werning, 2019). For example, Hunt et al (2013) showed participants visual contexts in which an agent affected none of one group of referents (i.e., the brownies in the lower example), all of another group (i.e., the tomatoes in the lower example), and some‐but‐not‐all of the third group (i.e., the steaks in the lower example); see Figure 1.…”
Section: What Previous Event‐related Potential Studies Have Shownmentioning
confidence: 99%
“…In fact, much electrophysiological research on scalar implicatures is already using this approach. The body of research examining how the realization of a scalar inference modulates processing of words downstream (Hunt et al, 2013; Nieuwland et al, 2010; Noveck & Posada, 2003; Sikos, Tomlinson, Traut, & Grodner, 2013; Spychalska et al, 2016, 2019), summarised above, exemplifies an instrumental approach: such studies were never intended to show what is happening in the brain when a scalar implicature is actually realised, but rather were intended to use downstream brain responses as an instrument to detect whether or not an inference had been realised earlier. The interpretation of these results is, accordingly, more straightforward than the interpretation of much of the rest of the electrophysiological literature discussed above.…”
Section: An Alternative Approachmentioning
confidence: 99%